Floatable silver cluster gel composite catalyst as well as preparation method and application thereof in CO2 reduction field
By combining silver clusters with gels that polymerize ionic liquids of imidazole halogen salts, floating silver cluster gel composite catalysts are prepared, which solves the problems of low stability and recycling rate of traditional photocatalysts and significantly improves photocatalytic CO2 The efficiency and stability of reduction have industrial prospects.
Patent Information
- Application Number
- CN202411348428.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional photocatalysts have defects in stability, recycling rate and efficiency, which leads to difficulties in large-scale applications, especially silver cluster photocatalysts are difficult to separate and recover due to their small size and easy to agglomerate and poor stability.
By combining silver clusters with gels formed by polymerizing high-stability imidazole halogen salt ionic liquid, a floating silver cluster gel composite catalyst is prepared, using the three-dimensional network structure and hydrophobic-low density characteristics of the gel. The silver clusters are stabilized and bounded in the gel, improving their stability and durability during the catalytic process.
It significantly improves the stability and reuse rate of silver cluster photocatalysts, increases the specific surface area and carrier transmission performance, significantly improves the efficiency of photocatalytic CO2 reduction, and has the advantages of green, environmentally friendly, low consumption and high efficiency.
Smart Images

Figure CN119259116A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a floating silver cluster gel composite catalyst, a preparation method thereof, and an application thereof in the field of CO2 reduction.
[0002] The present invention belongs to the 3.1 New Functional Materials Industry Key Direction under 3.1.12 New Catalytic Materials and Additives, New Photocatalytic Materials and Other Additives in the 3 New Materials Industry of the Catalogue of Strategic New Industries. Background Art
[0003] With the emergence of a series of problems such as energy shortage and environmental pollution, humans have begun to pursue clean energy and environmental protection. Photocatalysis, as a new type of green energy conversion pathway, has attracted much attention and become a hot topic for many scholars. At present, traditional photocatalytic materials are divided into two types: one is to use nano-scale powdered materials as catalysts and evenly disperse them in water; the other is to fix the catalytic material and allow pollutants to flow on the catalyst surface for reaction. However, these traditional catalytic systems have serious reverse reactions, active ingredients are easily leached during continuous testing, and have poor stability. In particular, powdered materials are difficult to recycle and are prone to secondary pollution. The fixed photocatalyst has low light energy efficiency, which makes it difficult to apply photocatalytic technology on a large scale and hinders the development of traditional photocatalysis.
[0004] A new and efficient photocatalytic system - floating photocatalyst has the opportunity to solve the above dilemma. Compared with traditional catalysts, floatable photocatalysts have unique advantages such as easy recycling and reuse, overcome the limitations and disadvantages of powder materials and fixed photocatalysts, and have a large effective specific area and good photocatalytic performance. Therefore, considering the theoretical and practical significance of improving the efficiency and comprehensive availability of photocatalysts, the research on floatable catalysts represents a new field worthy of in-depth exploration and continuous development. However, the development of floating photocatalysts is still in its infancy, and the defects of low sunlight utilization, insufficient active sites, and low proportion of active components have led to unsatisfactory photocatalytic efficiency. The self-supporting floating photocatalyst as an active component is restricted by factors such as high requirements and difficulty of synthesis technology. Therefore, it is of great significance to develop a suitable and simple method for preparing efficient and stable self-floating photocatalysts.
[0005] In recent years, atomically precise metal nanoclusters have shown great application prospects in the field of solar energy collection and conversion due to their unique atomic stacking patterns, quantum confinement effects, and abundant catalytic active sites. Among them, silver cluster photocatalysts, as a catalytic material with unique structure and properties, have significant advantages in the field of photocatalysis. First, silver cluster photocatalysts have a molecular-like discrete band structure and can be regarded as narrow bandgap semiconductors. They can efficiently absorb visible and ultraviolet light and convert them into chemical energy for catalytic reactions. In addition, the nanostructure of silver cluster photocatalysts can provide a large number of catalytic active sites, which can effectively contact with reactants and catalyze reactions, thereby improving photocatalytic efficiency. However, due to the small size of silver clusters (about 1.4 nm), they are easy to agglomerate, so their stability is poor. In addition, small-sized silver clusters are difficult to separate when dispersed in water, and the recycling rate is too low.
[0006] In order to further improve the photocatalytic activity, recycling rate and stability of silver clusters, they can be compounded with porous gel active components composed of highly stable polyionic liquids to prepare multiphase photocatalysts. The unique hydrophobic-low density properties of the gel can also ensure that the catalyst floats on the water surface, which helps to increase the contact area between the reactants and the photocatalyst, thereby optimizing the "light-material-substrate" interface reaction process and facilitating the aerophilic and hydrophobic photocatalytic CO2 reduction reaction. In addition, through the ionic interaction between the surface ligands of the silver clusters and the ionic liquids, the silver clusters can be effectively and stably bound to the gel network. This design can significantly improve the stability and durability of the silver clusters during the catalytic process, which is of great significance for the long-term use and industrial application of the catalyst. However, there are currently no reports on the preparation of floating photocatalysts by compounding silver clusters with gel complexes. Summary of the invention
[0007] In order to improve the stability and durability of silver cluster photocatalysts in the catalytic process, the present invention provides a high specific surface area, high performance, high stability floatable silver cluster gel multiphase composite catalyst and a preparation method thereof, as well as application in the field of photocatalytic CO2 reduction.
[0008] The object of the present invention is achieved in the following manner: a floating silver cluster gel composite catalyst, wherein the silver clusters interact with the halogen ions in the gel through their surface ligands, so that the silver clusters are confined in the three-dimensional network structure of the gel, and the gel is polymerized from imidazole halogen salt ionic liquid.
[0009] The preparation method of the floatable silver cluster gel composite catalyst comprises the following steps: (1) Preparation of silver cluster solution Thiosalicylic acid and silver nitrate were dissolved in deionized water at a molar ratio of (1-3):1, and ultrasonicated to fully dissolve them. Then, 25% volume concentration of NH3 was added to the solution.. The volume ratio of H2O, deionized water and ammonia water is (6-18):1, and ultrasonic dispersion is performed to obtain a yellow transparent solution; (2) Add a crosslinking agent and an azo initiator to a solvent N,N-dimethylformamide, respectively, and then add an imidazole halogen salt ionic liquid thereto, wherein the molar ratio of the imidazole halogen salt ionic liquid, the initiator, the crosslinking agent and the solvent is (1-10): (0.1-0.6): (0.5-2.5): (200-350), and then add the silver cluster solution prepared in step (1), wherein the volume mass ratio of the silver cluster solution to the imidazole halogen salt ionic liquid is (0.2-1.0): 0.31, and stir at room temperature for 30-120 minutes. Then, add the above solution to a reactor and react at 160-200° C. for 8-48 hours. After the reaction is completed, add N,N-dimethylformamide and soak for 2-4 days; and dry under vacuum at 60-80° C. for 6-12 hours to obtain a floating silver cluster gel composite catalyst.
[0010] The imidazole halogen salt ionic liquid is any one of 1-vinyl-3-butyl imidazole bromide, 1,3-dibutyl imidazole iodide and 1,3-dioctyl imidazole chloride.
[0011] The initiator is any one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
[0012] The cross-linking agent is any one of ethylene glycol dimethacrylate, bisacrylamide and divinylbenzene.
[0013] Application of floatable silver cluster gel composite catalyst for photocatalytic CO2 reduction reaction.
[0014] Compared with the prior art, the present invention successfully prepares a high specific surface area, high performance, and high stability floating silver cluster gel composite catalyst by a simple hydrothermal method, and the operation is simple. Silver clusters are added to the preparation process of the gel, and the silver cluster surface ligands interact with the halogen ions in the gel to stably confine the silver clusters in the three-dimensional network structure of the gel polymerized by the imidazole halogen salt ionic liquid, thereby obtaining a floating silver cluster gel composite catalyst. After the gel is loaded with the silver cluster photocatalyst, the photocatalytic performance of the catalyst is improved through ionic interaction, and the loss of the silver cluster photocatalyst is successfully prevented, making it easy to separate and reuse in the catalytic process; the loose and porous structure of the gel provides more reactive sites for the photocatalytic reaction, improves the specific surface area and carrier transport performance of the catalyst; after the gel is combined with the silver cluster, it ensures that the catalyst has a good structure and photocatalytic stability. Compared with silver clusters and gels, the photocatalytic CO2 reduction performance of the floating silver cluster gel composite catalyst is significantly improved, and it has the advantages of being green, environmentally friendly, low-consumption, high-efficiency, and having good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of the preparation process and morphology of the floating silver cluster gel composite catalyst.
[0016] Figure 2 This is a transmission electron micrograph of the gel.
[0017] Figure 3 These are the transmission electron microscope photos, mass spectra and particle size distribution diagrams of silver clusters.
[0018] Figure 4 It is a transmission electron microscope photograph of the floatable silver cluster gel composite catalyst prepared in Example 1 and a particle size distribution diagram of the silver clusters in the floatable silver cluster gel composite catalyst.
[0019] Figure 5 This is an EDS-Mapping photograph of the floatable silver cluster gel composite catalyst prepared in Example 1.
[0020] Figure 6 It is the XRD curve diagram of the silver cluster, gel and the floatable silver cluster gel composite catalyst prepared in Example 1.
[0021] Figure 7 It is the photocatalytic efficiency of the silver cluster, the gel and the floatable silver cluster gel composite catalyst prepared in Examples 1-3.
[0022] Figure 8 It is the photocatalytic efficiency of the floatable silver cluster gel composite catalyst prepared in Example 4-7.
[0023] Fig. 9 is the contact angle of the silver cluster, the gel and the floatable silver cluster gel composite catalyst prepared in Example 1.
[0024] Fig.10 The solid UV, BET, LSV, impedance and photocurrent curves of the silver cluster, gel and the floatable silver cluster gel composite catalyst prepared in Example 1 are shown. DETAILED DESCRIPTION
[0025] A floating silver cluster gel composite catalyst, wherein the silver clusters interact with the halogen ions in the gel through their surface ligands, so that the silver clusters are confined in the three-dimensional network structure of the gel, and the gel is polymerized from imidazole halogen salt ion liquid.
[0026] The method for preparing the above-mentioned floatable silver cluster gel composite catalyst comprises the following steps: (1) Preparation of silver cluster solution Dissolve thiosalicylic acid and silver nitrate in deionized water at a molar ratio of (1-3):1, sonicate to dissolve them fully, and then add 25% volume concentration of NH3 .The volume ratio of H2O, deionized water and ammonia water is (6-18):1, and ultrasonic dispersion is performed to obtain a yellow transparent solution; the amount of deionized water used is sufficient to fully dissolve thiosalicylic acid and silver nitrate, and a slight excess can also be used. NH3 . The purpose of H2O is to keep the solution in a slightly alkaline environment.
[0027] (2) Add a crosslinking agent and an azo initiator to a solvent N,N-dimethylformamide, respectively, and then add an imidazole halogen salt ionic liquid thereto, wherein the molar ratio of the imidazole halogen salt ionic liquid, the initiator, the crosslinking agent and the solvent is (1-10): (0.1-0.6): (0.5-2.5): (200-350), and then add the silver cluster solution prepared in step (1), wherein the volume mass ratio of the silver cluster solution to the imidazole halogen salt ionic liquid is (0.2-1.0) mL: 0.31 g, and stir at room temperature for 30-120 min. Then, add the above solution to a reactor and react at 160-200° C. for 8-48 h. After the reaction is completed, add N,N-dimethylformamide and soak for 2-4 days; and dry under vacuum at 60-80° C. for 6-12 h to obtain a floating silver cluster gel composite catalyst.
[0028] The imidazole halogen salt ionic liquid is any one of 1-vinyl-3-butyl imidazole bromide, 1,3-dibutyl imidazole iodide and 1,3-dioctyl imidazole chloride.
[0029] The initiator is any one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
[0030] The cross-linking agent is any one of ethylene glycol dimethacrylate, bisacrylamide and divinylbenzene.
[0031] The above-mentioned floatable silver cluster gel composite catalyst is used for photocatalytic CO2 reduction reaction.
[0032] Preparation method of silver cluster solution: 155 mg thiosalicylic acid and 170 mg silver nitrate (molar ratio of 1:1) were dissolved in 6 mL deionized water, ultrasonicated for 20 min to fully dissolve thiosalicylic acid and silver nitrate, and then 0.5 mL of 25% NH3 . H2O, ultrasonic for 20 min, NH3 . H2O was evenly dispersed to obtain a yellow transparent silver cluster solution.
[0033] Preparation method of gel: 2.0 g of cross-linking agent ethylene glycol dimethacrylate (EGDMA) and 0.05 g of initiator azobisisobutyronitrile (AIBN) were added to 20 mL of solvent N,N-dimethylformamide (DMF), and then 0.31 g of ionic liquid 1-vinyl-3-butylimidazolium bromide (IL-EVIBr) was added. The mixture was stirred at room temperature for 30 min, and then the above solution was added to the reactor and reacted at 180°C for 24 h. After the reaction was completed, DMF was added and soaked for 2 to 4 days, and finally dried at 80°C under vacuum conditions for 12 h to obtain a gel.
[0034] Example 1 The preparation method of a floatable silver cluster gel composite catalyst comprises the following steps: adding 2.0 g of a cross-linking agent ethylene glycol dimethacrylate (EGDMA) and 0.05 g of an initiator azobisisobutyronitrile (AIBN) into 20 mL of a solvent N,N-dimethylformamide (DMF), then adding 0.31 g of an ionic liquid 1-vinyl-3-butylimidazolium bromide (IL-EVIBr) (the molar ratio of the ionic liquid, the initiator, the cross-linking agent and the solvent is 10: 0.3: 1.3: 273), and then adding 0.6 mL of a silver cluster solution prepared by the above-mentioned preparation method of the silver cluster solution, stirring at room temperature for 30 min, then adding the above-mentioned mixed solution into a reactor, reacting at 180° C. for 24 h, adding DMF to soak for 3 days after the reaction is completed, and finally drying at 80° C. under vacuum conditions for 12 h to obtain a floatable silver cluster gel composite catalyst.
[0035] Figure 1 This is a flow chart of the preparation of floating silver cluster gel composite catalyst. Figure 1 It can be seen that in the obtained floatable silver cluster gel composite catalyst, the silver clusters are dispersed in the three-dimensional interpenetrating network structure of the gel polymerized by 1-vinyl-3-butylimidazolium bromide ionic liquid.
[0036] Figure 2 is a TEM image of the gel. Figure 2 It can be seen that after hydrothermal crosslinking, the ionic liquid forms a porous and loose gel with a size between 100 nm and 1 μm, which is abbreviated as PILS below. Figure 3 TEM images, mass spectra and particle size distribution of silver clusters. Figure 3 a and Figure 3 c It can be seen that the silver clusters are small particles with an average particle size of 1.4 nm. Figure 3 b It can be seen that the molecular weight of the silver cluster is 2196, so its molecular formula is inferred to be [Ag9(mba)8H8] + , hereinafter abbreviated as Ag9.
[0037] Figure 4TEM image of the floatable silver cluster gel composite catalyst prepared in Example 1 and the particle size distribution diagram of the silver clusters in the floatable silver cluster gel composite catalyst. Figure 4 From ab, we can see that silver cluster nanoparticles are evenly dispersed inside the three-dimensional network structure of the gel. Figure 4 c It can be seen that the average particle size of the silver cluster nanoparticles dispersed inside the three-dimensional network structure of the gel is 1.35 nm. Figure 5 This is an EDS-Mapping photo of the floatable silver cluster gel composite catalyst. It can be seen that the main component of the floatable silver cluster gel composite catalyst is C element and a small amount of N element. The silver element is also evenly distributed on the surface of the floatable silver cluster gel composite catalyst.
[0038] Figure 6 Figure 1 is the XRD spectra of the silver clusters, gel and the floatable silver cluster gel composite catalyst prepared in Example 1. Due to the small size of the silver clusters, no obvious diffraction peaks were detected. However, Figure 3 b The mass spectrum of silver clusters shows that the main component of silver clusters is Ag; the gel has a wide characteristic diffraction peak at about 20 degrees, indicating that the gel is mainly carbon material; the diffraction peak of the floating silver cluster gel composite catalyst is consistent with the gel, and no other impurity peaks appear. No silver cluster peaks are detected in the composite, which is mainly due to the small size of the silver clusters, weak peaks and low content. XRD confirms that the main components of the gel and the composite are carbon materials.
[0039] Example 2 Compared with Example 1, the difference is that the amount of the silver cluster solution added is 0.2 mL.
[0040] Example 3 Compared with Example 1, the difference is that the amount of the silver cluster solution added is 1 mL.
[0041] Example 4 Compared with Example 1, the difference is that the crosslinking agent is divinylbenzene (DVB).
[0042] Example 5 Compared with Example 1, the difference is that the cross-linking agent is bisacrylamide (MBA).
[0043] Example 6 Compared with Example 1, the difference is that the initiator is azobisisoheptanonitrile.
[0044] Example 7 Compared with Example 1, the difference is that the ionic liquid is 1,3-dibutylimidazolium iodide.
[0045] Example 8 The molar ratio of ionic liquid 1-vinyl-3-butylimidazolium bromide, initiator dimethyl azobisisobutyrate, crosslinking agent ethylene glycol dimethacrylate and solvent DMF is 8:0.6:2.5:350, and then the silver cluster solution prepared by the preparation method of the above silver cluster solution is added, the molar ratio of thiosalicylic acid to silver nitrate is 2:1 when preparing the silver cluster solution, and the volume mass ratio of the silver cluster solution to the imidazole halogen salt ionic liquid is 0.8 mL:0.31 g, and the mixture is stirred at room temperature for 120 min. Then, the above solution is added into a reactor and reacted at 160°C for 48 h. After the reaction is completed, N,N-dimethylformamide is added and soaked for 2 days; and dried at 60°C under vacuum for 6 h to obtain a floating silver cluster gel composite catalyst.
[0046] Example 9 Compared with Example 1, the difference is that the molar ratio of thiosalicylic acid to silver nitrate is 3:1.
[0047] The molar ratio of ionic liquid 1,3-dioctyl imidazolium chloride, initiator AIBN, crosslinker EGDMA and solvent DMF is 1:0.1:0.5:200, and then the silver cluster solution prepared by the above-mentioned silver cluster solution preparation method is added, and the volume mass ratio of the silver cluster solution to the imidazole halogen salt ionic liquid is 0.5mL:0.31g. Stir at room temperature for 60min, then add the above solution into a reactor, and react at 200℃ for 8h; after the reaction, add N,N-dimethylformamide and soak for 4 days; dry under vacuum at 70℃ for 8h to obtain a floating silver cluster gel composite catalyst.
[0048] CO2 photocatalytic reduction experiment The silver cluster solution, gel and the floatable silver cluster gel composite catalyst prepared in Examples 1 to 7 were subjected to CO2 photocatalytic reduction experiments under the same conditions, specifically: the silver cluster solution, gel or floatable silver cluster gel composite catalyst was added to 45 ml of water for ultrasonic dispersion, and then 5 ml of triethanolamine was added, ultrasonicated for 5 minutes, CO2 was continuously passed for ten minutes, and then a 300 W xenon lamp was turned on, and samples were taken at regular time intervals. The peak area of CO in the chromatogram was detected by a photocatalytic online evaluation system, and the overall performance of the photocatalytic carbon dioxide reduction was calculated using a standard curve.
[0049] Figure 7 The photocatalytic CO2 reduction activity diagram of the silver cluster, gel and the floatable silver cluster gel composite catalyst prepared in Examples 1-3. Figure 7It can be seen that the activity of silver clusters and gel is very low. This is because pure silver clusters have poor stability, low specific surface area, and easy carrier recombination; while the gel is white and cannot fully absorb and utilize sunlight. After the silver clusters and gel are combined, not only the utilization rate of sunlight is improved, but also the specific surface area and carrier transport performance are improved, thus significantly improving the photocatalytic CO2 reduction activity. When the volume mass ratio of silver cluster solution to imidazole halogen salt ionic liquid is 0.6mL:0.31g, the photocatalytic efficiency is the highest, and the 5-hour photocatalytic efficiency is 58.55 μmol / g, which is significantly higher than the photocatalytic efficiency of silver clusters and gel.
[0050] Figure 8 The photocatalytic CO2 reduction activity diagram of the floatable silver cluster gel composite catalyst prepared in Examples 4 to 7. When the cross-linking agent is replaced with divinylbenzene (DVB) and MBA (bisacrylamide), the 5-hour photocatalytic CO2 efficiency is 19.5 μmol / g and 52.25 μmol / g respectively; when the initiator is azobisisoheptanenitrile, the 5-hour photocatalytic CO2 efficiency is 48.23 μmol / g respectively; when the ionic liquid is 1,3-dibutylimidazolium iodide, the 5-hour photocatalytic CO2 efficiency is 13.79 μmol / g, which are significantly higher than the photocatalytic efficiency of silver clusters and gels.
[0051] Fig. 9 The contact angle images of the silver cluster, gel and the floatable silver cluster gel composite catalyst prepared in Example 1 show that the gel is a hydrophobic structure, while the silver cluster has abundant carboxyl groups on its surface, so the contact angle is less than 90 degrees, which is hydrophilic. After the silver cluster and the gel are combined to form a floatable silver cluster gel composite catalyst, the overall hydrophobicity is presented. This aerophilic and hydrophobic catalyst is more suitable for CO2 reduction reaction and can effectively reduce the occurrence of side reactions such as hydrogen evolution. After the silver cluster and the gel are combined to form a floatable silver cluster gel composite catalyst, the silver clusters in the floatable silver cluster gel composite catalyst dissolve in water in the CO2 reduction reaction, while the gel floats on the water surface, forming a multiphase structure, which significantly improves the reuse rate of the catalyst.
[0052] Fig.10 The UV absorption, BET, CO2 adsorption, LSV, impedance and photocurrent curves of the silver cluster, gel and the floatable silver cluster gel composite catalyst prepared in Example 1 are shown in FIG. Fig.10 a It can be seen that the gel can only absorb ultraviolet light, while the silver cluster has a good ultraviolet-visible light absorption capacity. After the two are combined, the sunlight absorption utilization rate of the floating silver cluster gel composite catalyst is significantly improved compared with the gel, which is conducive to the generation of more photogenerated carriers. Fig.10 As can be seen from b, the silver clusters have a very small specific surface area, while the gel has a three-dimensional loose and porous network structure with a large specific surface area. After the gel is loaded with silver clusters, the specific surface area is further increased, which is beneficial to increase the surface active sites. Fig.10 c It can be seen that the floating silver cluster gel composite catalyst has the strongest CO2 adsorption capacity, laying the foundation for improving the carbon dioxide reduction activity. Fig.10 It can be seen that the floatable silver cluster gel composite catalyst has the strongest photocurrent and the smallest charge transfer resistance, indicating that the carrier transport performance of the floatable silver cluster gel composite catalyst is significantly improved compared with silver clusters and gel.
[0053] The present invention successfully prepares a silver cluster gel floatable multiphase photocatalyst with high specific surface area, high performance and high stability through a simple hydrothermal method, which is simple to operate and novel in structure. The combination of silver clusters and gel effectively improves the specific surface area, sunlight utilization rate, number of active sites and carrier transport performance of the composite catalyst; in addition, the stability and dispersibility of the silver clusters are improved by utilizing the ionic interaction between the silver clusters and the gel and the porous network structure of the gel. After the silver clusters are combined with the gel to form a floatable silver cluster gel composite catalyst, the silver clusters in the floatable silver cluster gel composite catalyst are dissolved in water in the CO2 reduction reaction, while the gel floats on the water surface to form a multiphase structure, which significantly improves the reuse rate of the catalyst. Therefore, the photocatalytic CO2 reduction activity of the floatable silver cluster gel composite catalyst is significantly improved, the structural stability is good, and it has the advantages of being green, environmentally friendly, low-consumption, high-efficiency and having good industrial prospects.
[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.
Claims
1. A floating silver cluster gel composite catalyst, characterized in that: The silver clusters interact with the halogen ions in the gel through their surface ligands, so that the silver clusters are confined in the three-dimensional network structure of the gel. The gel is polymerized from imidazole halogen salt ionic liquid.
2. The method for preparing the floatable silver cluster gel composite catalyst according to claim 1, characterized in that: The process comprises the following steps: (1) preparing a silver cluster solution Thiosalicylic acid and silver nitrate were dissolved in deionized water at a molar ratio of (1-3):1, and ultrasonicated to fully dissolve them. Then, 25% volume concentration of NH3 was added to the solution. . The volume ratio of H2O, deionized water and ammonia water is (6-18):1, and ultrasonic dispersion is performed to obtain a yellow transparent solution; (2) Add a crosslinking agent and an azo initiator to a solvent N,N-dimethylformamide, respectively, and then add an imidazole halogen salt ionic liquid thereto, wherein the molar ratio of the imidazole halogen salt ionic liquid, the initiator, the crosslinking agent and the solvent is (1-10): (0.1-0.6): (0.5-2.5): (200-350), and then add the silver cluster solution prepared in step (1), wherein the volume mass ratio of the silver cluster solution to the imidazole halogen salt ionic liquid is (0.2-1.0): 0.31, and stir at room temperature for 30-120 minutes. Then, add the above solution to a reactor and react at 160-200° C. for 8-48 hours. After the reaction is completed, add N,N-dimethylformamide and soak for 2-4 days; and dry under vacuum at 60-80° C. for 6-12 hours to obtain a floating silver cluster gel composite catalyst.
3. The method for preparing the floatable silver cluster gel composite catalyst according to claim 2, characterized in that: The imidazole halogen salt ionic liquid is any one of 1-vinyl-3-butyl imidazole bromide, 1,3-dibutyl imidazole iodide and 1,3-dioctyl imidazole chloride.
4. The method for preparing the floatable silver cluster gel composite catalyst according to claim 2, characterized in that: The initiator is any one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
5. The method for preparing the floatable silver cluster gel composite catalyst according to claim 2, characterized in that: The cross-linking agent is any one of ethylene glycol dimethacrylate, bisacrylamide and divinylbenzene.
6. The use of the floatable silver cluster gel composite catalyst as claimed in claim 1, characterized in that: Used for photocatalytic CO2 reduction reaction.